2009
DOI: 10.1542/peds.2008-3141
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Home Versus Temporary Housing: The Importance of a Stable Usual Source of Care

Abstract: Introduction Recent health care reform policies focus on finding the best medical home for everyone. Less is known about how the stability of a usual source of care (USC) over time impacts on structural access to care. Objectives To examine the prevalence of USC changes among a low-income population of children, and how these changes were associated with unmet need. Design and Methods Cross-sectional, multivariable analyses of mail-return survey data from Oregon's food stamp program in January 2005. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
2
25
1
1
Order By: Relevance
“…24,25 An enduring relationship between the patient and his or her usual source of care also appears to be associated with better quality. 26 There is also evidence that patients with a "regular doctor" as a usual source of care, rather than a "regular practice site," are more likely to receive preventive services. 25,27,28 As compared to quality, the relationship between health outcomes and having a usual source of primary care has been less well studied.…”
Section: Primary Care As a Set Of Functionsmentioning
confidence: 99%
“…24,25 An enduring relationship between the patient and his or her usual source of care also appears to be associated with better quality. 26 There is also evidence that patients with a "regular doctor" as a usual source of care, rather than a "regular practice site," are more likely to receive preventive services. 25,27,28 As compared to quality, the relationship between health outcomes and having a usual source of primary care has been less well studied.…”
Section: Primary Care As a Set Of Functionsmentioning
confidence: 99%
“…We reported on cross-sectional measures for both insurance and a USC because we did not have data to capture longitudinal USC status; therefore, we could not capture the effects of duration of insurance and/or continuity with a USC. [55][56][57] We also did not account for the type of USC provider, which might contribute to subtle differences that were not measured in this study. 58 Also, we did not include a full analysis of the specific reasons people reported a lack of a USC; however, upon review of the main reasons we found the top reported to be that respondents were seldom or never sick and the second most common was that the cost of medical care was too high.…”
Section: Limitationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Children with a USC have more consistent access to health care services, 2,9,[11][12][13][14][15] which likely contributes to better overall health outcomes. 16,17 According to recent estimates, however, approximately 19% of adults and nearly 10% of children in the United States do not have a USC.…”
Section: Introductionmentioning
confidence: 99%